Determinasi Kualitas Audit pada Aparat Pengawas Intern Pemerintah (APIP): (Studi Empiris pada Inspektorat Provinsi Maluku) - Dirk Berly Tehuayo; Evandro Adolf Willem Manuputty (P3M Politeknik Negeri Ambon, 2026)
This study aims to examine the effect of independence, competence, due professional care, and accountability on audit quality within the Internal Government Supervisory Apparatus (APIP). A quantitative approach was employed using a survey method by distributing questionnaires to auditors of the Inspectorate of Maluku Province. The sample consisted of 60 auditors selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that independence, competence, due professional care, and accountability have a positive and significant effect on audit quality, both partially and simultaneously. Accountability emerged as the most dominant factor influencing audit quality. These findings suggest that audit quality is not only determined by auditors’ technical competence but also by personal characteristics such as integrity and professional responsibility. This study implies that improving audit quality within APIP should focus on strengthening auditor independence, enhancing competencies through continuous training, and fostering a culture of accountability within internal government oversight institutions.Keywords: independence, competence, due professional care, accountability, audit quality, internal audit